(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
This paper seeks to better understand the production of meanings in the context of online activism. Based on an interpretative and exploratory qualitative investigation approach, we seek to examine the path of the activist campaign “Cedae, this bill is not mine”, by the organization Meu Rio, in the context of the crisis of water supply to the metropolitan population of Rio de Janeiro, in early 2020. The study analyzes different strategies for mobilization and engagement in digital social networks and interprets the interpretation of people, from a web of interactions in search of meanings. The investigation takes place under the aegis of a larger interpretive category, sustainability, as the transformations that one wants to see in the world depend on actions that involve social mobilization for change. Activism thus reveals itself as an emerging and fundamental activity for the design and expansion of communication practices in sustainable development.